The Functional Components and Hepatic Protective Mechanism of Wolfberry Vinegar by Mixed-Culture Fermentation - Xiao Qiang; Man Zhao; Ting Xia; Qi Wang; Junwei Yu; Yunru Song; Huimin Zhang; Changsheng Qiao; Min Wang (Foods)
Wolfberry (Lycium barbarum L.), as a kind of combination of medicine and food, is rich in antioxidant components. However, the deep-processed products of wolfberry need to be developed to improve its added value. This study aimed to investigate the nutrients, active antioxidant ingredients, and liver-protective mechanism of mixed-culture fermented wolfberry vinegar (MFV). The results showed that MFV had significantly higher protein and significantly lower fat content than wolfberry juice before fermentation, indicating that MFV was a healthy product. The active ingredient content, which included total phenolics, total flavonoids, polysaccharides, betaine, and antioxidant activities, was significantly increased in MFV after mixed-culture fermentation. Moreover, MFV improved histopathological changes and reduced liver biochemical indicators in alcohol-treated mice, indicating the improvement of liver function. In addition, MFV effectively alleviated alcohol-induced liver injury by increasing the expression of alcohol metabolizing enzymes and inhibiting CYP2E1 activity. MFV regulated the equilibrium between pro-oxidant and antioxidant levels by downregulating pro-oxidant markers and upregulating antioxidant markers. Furthermore, MFV reduced the levels of inflammatory indexes by inhibiting the PI3K/Akt/NF-κB signaling pathway. These results suggest that MFV is a healthy food for liver protection, which provides a strategy for deep-processed products of wolfberry.